Pre-Diagnostic Circulating Vitamin D and Risk of Melanoma in Men - Major, Jacqueline M.; Kiruthu, Christine; Weinstein, Stephanie J.; Horst, Ronald L.; Snyder, Kirk; Virtamo, Jarmo; Albanes, Demetrius (PLOS ONE, 2012)
Purpose Various studies have examined the association between serum vitamin D levels and different cancers; however, this is the first prospective study of this association with melanoma risk. The aim of this study is to investigate the association between serum vitamin D [25(OH)D] levels and melanoma in a cohort of older, middle-aged Finnish male smokers. Methods We conducted a nested case-control study within the Alpha-Tocopherol Beta-Carotene Cancer Prevention (ATBC) Study. From the ATBC cohort, 368 subjects were chosen for our study; 92 participants that developed melanoma and 276 matched control subjects. At study baseline, lifestyle questionnaires and blood samples were collected. Serum 25(OH)D was modeled as three sets of categorical variables: clinically-defined categories, season-specific quartiles and season-adjusted residual quartiles. Conditional logistic regression was used to obtain odds ratios (ORs) and 95% confidence intervals (95% CIs) to estimate the association between circulating vitamin D and melanoma risk. Results Overall no association of serum 25(OH)D and melanoma risk was observed. A decreased risk of developing melanoma was observed in the middle categories compared to the lowest category, albeit not significant. Conclusion Results indicate no association between serum 25(OH)D levels and melanoma. Additional studies, including possibly consortium efforts, are needed to investigate the association between serum 25(OH)D levels and risk of melanoma in larger, more diverse study populations.